Rancangan Sistem Informasi Penerimaan Siswa Baru SMP Swasta Generasi Kedde Wali Berbasis Web dengan Metode Waterfall - Getrudis Kaka Daha; NM Faizah; Widyat Nurcahyo (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
The aim of this research is; To improve and make it easier for prospective new student registration at Generation Kedde Wali Private Middle School, Availability of an online new student admission information system that has an attractive appearance and is easy to register, To facilitate the PSB process in filling in new student admissions through the website and automatically saved, there is no need anymore to fill in using handwriting, and to improve new student enrollment services at the Generation Kedde Wali Private Middle School. In this study, the data source used was data obtained from direct observation and conducting interviews with schools. The waterfall method was used at the application development stage, while the Data Flow Diagram (DFD) was used as an application design tool. The results of the study show that using a website-based information system can help smooth and facilitate new student registration compared to manual systems, so that it can be accurate and efficient in serving PPDB activities.